‘To what extent do legal frameworks in the UK better protect civil liberties and human rights that in Uzbekistan?’ - Mokhinur Rakhmatullaeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article provides a comparative analysis of legal frameworks in terms of civil liberties and human rights in two different countries. Since there have been emerging controversies regarding two different legal systems. It is true that in the UK over the past 20 years, there have been significant developments that have undermined public confidence in the human rights framework in the UK, and which make the change necessary today. The enforcement of different statutes and precedents lead to many changes in the UK. Meanwhile, Uzbekistan prima facie mentions the formal list of human rights and civil liberties through its Constitution and emphasizes their implementation within the standing normative-legal acts.